Influence of silane coupling agents on the rheological behavior of hemp fiber filled polyamide 1010 biomass composites in molten state (AIP conference proceedings, 2015)
In order to develop the new engineering materials such as structural materials and tribomaterials based on all plants-derived materials, the influence of silane coupling agent on the rheological properties of hemp fiber (HF) filled polyamide 1010 (PA1010) biomass composites in molten state was investigated for one step of the fabrication of these materials. PA1010 was made from sebacic acid and decamethylenediamine, which are obtained from plant-derived castor oil. Hemp fibers were surface-treated by two types of surface treatment: a) alkali treatment by NaOH solution and b) surface treatment by silane coupling agents with different concentrations. Three types of silane coupling agents: aminosilane, epoxysilane and ureidosilane were used for surface treatment. HF/PA1010 composites were extruded by a twin screw extruder and compression-molded. Rheological behavior in molten state were evaluated by oscillatory flow testing using a parallel plate type rheometer. It was found that the silane coupling agents remarkably influence on: 1) rheological properties such as storage modulus, loss modulus, loss tangent and complex viscosity in low angular frequency region in molten state, 2) temperature dependences of rheological properties, and 3) relationship between phase angle and complex modulus (van Gurp – Palmen plots). These rheological behavior were also strongly influenced by the type of silane coupling agents. The viscoelastic properties (both storage and loss moduli) of aminosilane and epoxysilane treated composites were lower, however, those of ureidosilane treated ones were higher than the moduli of only alkali treated composites. Ureidosilane treated composites were the least temperature sensitive in the surface treated composites investigated here.